2022
DOI: 10.1186/s13007-022-00972-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification and PEG-mediated transient expression of mesophyll protoplasts in Camellia oleifera

Abstract: Background Camellia oleifera (C. oleifera) is a woody edible oil crop of great economic importance. Because of the lack of modern biotechnology research, C. oleifera faces huge challenges in both breeding and basic research. The protoplast and transient transformation system plays an important role in biological breeding, plant regeneration and somatic cell fusion. The objective of this present study was to develop a highly efficient protocol for isolating and purifying mesophyll protoplasts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 73 publications
3
8
0
Order By: Relevance
“…In our system, the most effective transfection time for passion fruit protoplast is 5 min (Fig. 3C, D), which is consistent with the optimization results for Magnolia (Shen et al, 2017), but different from Camellia oleifera, Chinese cabbage and cassava (Wu et al, 2017;Sivanandhan et al, 2021;Li et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our system, the most effective transfection time for passion fruit protoplast is 5 min (Fig. 3C, D), which is consistent with the optimization results for Magnolia (Shen et al, 2017), but different from Camellia oleifera, Chinese cabbage and cassava (Wu et al, 2017;Sivanandhan et al, 2021;Li et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…2A, B), which is consistent with that of grape and camellia protoplast. However, the plasmid DNA required for optimal passion fruit protoplast transfection was about twofold lower (Wang et al, 2015;Zhao et al, 2016;Li et al, 2022). In this study, we found that a passion fruit protoplast density of 1.0 × 10 6 cells/ml resulted in the best transformation efficiency (Fig.…”
Section: Discussionmentioning
confidence: 46%
“…Protocols for the isolation and purification of protoplasts from tea leaves have been reported [12,13]. However, the separation efficiency remains relatively low and experimental replicability is poor; moreover, these protocols do not apply to the preparation of protoplasts from the roots and branches of tea plants.…”
Section: Optimized Procedures For Protoplast Isolation and Purificationmentioning
confidence: 99%
“…All purification operations were conducted at 4 °C. Compared the previous results from Liu et al [12] and Peng et al [13], the procedures of protoplast isolation and purification were optimized with vacuum assisted treatment for improving enzymolysis efficiency, and only once rinsing.…”
Section: Optimized Procedures For Protoplast Isolation and Purificationmentioning
confidence: 99%
See 1 more Smart Citation